2012
DOI: 10.1186/1749-7922-7-s1-s10
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol acute intoxication before sepsis impairs the wound healing of intestinal anastomosis: rat model of the abdominal trauma patient

Abstract: IntroductionMost trauma patients are drunk at the time of injury. Up to 2% of traumatized patients develop sepsis, which considerably increases their mortality. Inadequate wound healing of the colonic repair can lead to postoperative complications such as leakage and sepsis.ObjectiveTo assess the effects of acute alcohol intoxication on colonic anastomosis wound healing in septic rats.MethodsThirty six Wistar rats were allocated into two groups: S (induction of sepsis) and AS (alcohol intake before sepsis indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Nevertheless, a previous study by our research group found that colonic anastomosis wound healing is impaired in rats with peritoneal sepsis and acute alcohol intake with the same alcohol exposure pattern used in the current study 12 . This suggests that diversion may be required if the intoxicated patient has fecal contamination and sepsis, as occurs in destructive colon trauma, for instance 12 .…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Nevertheless, a previous study by our research group found that colonic anastomosis wound healing is impaired in rats with peritoneal sepsis and acute alcohol intake with the same alcohol exposure pattern used in the current study 12 . This suggests that diversion may be required if the intoxicated patient has fecal contamination and sepsis, as occurs in destructive colon trauma, for instance 12 .…”
Section: Discussionmentioning
confidence: 75%
“…This suggests that diversion may be required if the intoxicated patient has fecal contamination and sepsis, as occurs in destructive colon trauma, for instance 12 . In our previous study, which included two groups (sepsis + alcohol and sepsis alone), the sepsis group exposed to alcohol exhibited poorer wound healing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This work was awarded the best paper at the 2011 Eastern Association for the Surgery of Trauma annual meeting. Another interesting manuscript reports on the role of alcohol and sepsis on the tensile strength of bowel anastomosis [ 7 ]. On novel diagnostic methods and therapies, Dr Sankarankutty reviewed the literature on the possible role of thromboelastometry [ 8 ] while another study reports on the lack of utility for recombinant factor VIIa in trauma [ 9 ].…”
mentioning
confidence: 99%